Investigation of the human metabolism and disposition of the prolyl hydrolase inhibitor daprodustat using IV microtracer with Entero‐Test bile string - Guoying Tai; Fangming Xia; Cathy Chen; Adrian Pereira; Jill Pirhalla; Xiusheng Miao; Graeme Young; Claire Beaumont; Liangfu Chen (Pharmacology Research & Perspectives, 2023)
Abstract Daprodustat is an oral small molecule hypoxia‐inducible factor (HIF) prolyl hydroxylase inhibitor (PHI) approved in Japan and the United States for the treatment of anemia associated with chronic kidney disease. This phase 1, nonrandomized, 2‐period, crossover study in 6 healthy men characterized and quantified the metabolites generated after a microtracer IV infusion of 50 μg (125 nCi) [14C]‐daprodustat administered concomitantly with a nonradiolabeled therapeutic dose of a 6‐mg daprodustat tablet, followed by a single oral solution dose of 25 mg (62.5 μCi) [14C]‐daprodustat. High‐performance liquid chromatography (HPLC) coupled with radioactivity detection (TopCount or AMS) and HPLC‐tandem mass spectrometry (HPLC‐MSn) were used for quantitative measurement and structural identification of radioactive metabolites in plasma, urine, feces, and bile. Following oral administration of [14C]‐daprodustat, unchanged daprodustat was the principal circulating drug‐related component, accounting for 40% of plasma radioactivity. Predominant oxidative metabolites M2, M3, M4, and M13 individually represented 6–8% of the plasma radioactivity and together accounted for the majority of radioactivity in urine and feces (53% in both matrices; 12% and 41% of dose, respectively). Unchanged daprodustat was not detected in urine and was only 0.7% of total radioactivity in feces (<0.5% of dose), with the remainder of the dose accounted for by oxidative metabolites. The radio‐metabolic profile of duodenal bile following IV infusion of [14C]‐daprodustat was similar to that observed in feces after oral administration. The data suggested that oral daprodustat was extensively absorbed, cleared exclusively by oxidative metabolism, and eliminated via hepatobiliary (primary) and urinary (secondary) excretion.